A Description on the Shake-Flask and Laser Monitoring-Based Techniques for Determination of the Drug's Solubility - Aynaz Zarghampour; Kimiya Jouyban; Vahid Jouyban-Gharamaleki; Abolghasem Jouyban; Elaheh Rahimpour (Tabriz University of Medical Sciences, 2024)
In the current work, the performance of the shake-flask and laser monitoring-based techniques for the determination of the solubility is described as a video file. The video is prepared in three parts. The first part is a general explanation of solubility and its manual and automatic measurement methods. The second part is about how to perform the shake-flask method to measure drug solubility, and the third part is about how the laser monitoring -based automatic device works to measure drug solubility.